The woman in black - Hill, Susan, 1942- (Vintage Books, 1998)
Arthur Kipps, a junior solicitor, is summoned to attend the funeral of Mrs Alice Drablow, the sole inhabitant of Eel Marsh House. The house stands at the end of a causeway, wreathed in fog and mystery, but it is not until he glimpses a wasted young woman, dressed all in black, at the funeral, that a creeping sense of unease begins to take hold, a feeling deepened by the reluctance of the locals to talk of the woman in black and her terrible purpose.